Six months chronic toxicity of Dryopteris filix –mas (L.) Schott ethanol leaf extract on Wistar rats - Earnest O Erhirhie; Emmanuel Emeka Ilodigwe (Journal of Herbal Drugs, 2022)
Background & Aim: Dryopteris filix-mas (D. filix-mas) is used among the Southern Nigerian populace in the management of rheumatoid arthritis, treatment of wounds, worm infestations, among other diseases. We evaluated the 6 months chronic exposure effects of its ethanol leaf extract in Wistar rat. Experimental: A total of 48 rats were randomized into four groups of 12 each as follows; group A (control) and the test groups B-D received 31.25, 62.5 and 125 mg/kg of the leaf extract, respectively. Blood samples were collected via retro-orbital puncture for baseline determination of haematological and biochemical parameters. Thereafter, rats were dosed orally (p.o) for 180 days (6 months) and blood samples were collected for the determination of haematological, biochemical parameters on the 181st day. Liver and kidneys were harvested for histopathology analyses. A 28 - day recovery study was also conducted to determine reversibility in toxicological effects. Results: There was no significant alteration (P>0.05) in heamatological, lipid profile and electrolyte parameters as well as body weight gain and relative organ weights of animals that were exposed to the extract when compared with control group. However, there was significant (P<0.005) reductions in alanine aminotransferase (ALT) and aspartate aminotransferase (AST) as well as elevation in urea and creatinine levels of extract treated groups. Histological sections did not reveal toxicity of liver architecture on day 181st, except dose dependent kidney toxicity, which was reversed following the recovery study. Recommended applications/industries: The leaf extract of Dryopteris filix-mas may be nephrotoxic following 6 months exposure.